1990
DOI: 10.1007/bf00686048
|View full text |Cite
|
Sign up to set email alerts
|

Platinum distribution inintraperitoneal tumors afterintraperitoneal cisplatin treatment

Abstract: The spatial distribution of platinum (Pt) in the kidney was studied by an autoradiographic technique, in which cisplatin (CDDP) was replaced by 195mPt-labeled CDDP, and by proton-induced X-ray emission (PIXE). Although both studies demonstrated comparable spatial distribution patterns, PIXE had the advantage that Pt concentrations could be determined quantitatively, in contrast to the relative information obtained by the autoradiographic technique. Using PIXE, the distribution of Pt in i.p. tumors was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1
3

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(75 citation statements)
references
References 18 publications
3
68
1
3
Order By: Relevance
“…Clinical studies reported that these patients have prolonged survival rates (15-17). One of the main advantage of IPC is better penetration of chemotherapeutic agents to the tumor nodules where the blood supply is poor (18). Intraperitoneal chemotherapy prevents micrometastases, local recurrence and distant metastases (2,19).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies reported that these patients have prolonged survival rates (15-17). One of the main advantage of IPC is better penetration of chemotherapeutic agents to the tumor nodules where the blood supply is poor (18). Intraperitoneal chemotherapy prevents micrometastases, local recurrence and distant metastases (2,19).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an adequate lymphadenectomy is essential. Intraperitoneal chemotherapy enters the peritoneal nodule by simple diffusion so it only penetrates to 1 or 2 mm [28] . It is not effective in lymph nodes.…”
Section: Prevention Protocols Using Perioperative Chemotherapy With Gmentioning
confidence: 99%
“…This model implies that there is an exponential concentration decrease of the drug from abdominopelvic cavity across the membrane to the plasma compartment. Consequently, the depth of penetration of the intraperitoneal concentration is very limited and is in the order of 1 to 2 mm [38,39] . Ozols et al [40] confirmed adriamycin penetrating only four to six cell layers of a tumor on the diaphragm in a rodent model.…”
Section: Tissue Distribution and Penetration Depthmentioning
confidence: 99%